In the "socialization scheme"- anthropology and historical materialism - Galor, Zbigniew (Anthropological Review, 1986)
An analysis of the mutual relations between anthropology and historical materialism permits to separate a certain method of solving the problems of human socialization, i.e. the "Socialization scheme" occuring in the investigation practice. Its theoretical premises are in the conception of man based on evolution theory and in the fact that in the works of K. Marx and F. Engels there occurs the anthropological theory of man (personalities, societies) formed under the conception of L. Feuerbach. In investigations this scheme favours the neglecting of the role of social structures in the formation of the features of the human individual. Decisive are here the nondialectic interpretations characteristic of the prescientific thought based on antinomies: changes and stability, determination and spontaneity, norms and activities. The cognitive perspective peculiar for the historical materialism assumes also the distinguishing of two types of social structures: the subjective structures and the anthropological structures. Contradicting to it are such conceptions as e.g. the conception of historical anthropology which by referring to the assumptions of historical materialism reduces however its premises to the theory of anthropogenesis or sociogenesis. Or it omits in the analyses the phenomenon of work contenting with the analysis of activities. In anthropological studies the "socialization scheme" does not favour an effective use of theories characteristic of historical materialism. Similarly it does not favour the utilization of the results of anthropological studies within this approach. It is visible by the fact that such studies use notions as e.g. need, generations, social environment which do not reflect adequately the social phenomena (in the sense in which they are used) or/and involve the terminology of evolutional anthropology.